Genetics of two colonies of Glossina pallidipes originating from allopatric populations in Kenya - Gooding, R.H.; Moloo, S.K. (Wiley, 1994)
Abstract Two large colonies, originating from allopatric populations of Glossina pallidipes Austen, in the Shimba Hills and Nguruman, Kenya, which differ biologically and with respect to vectorial competence, were compared at fourteen enzyme loci using polyacrylamide gel electrophoresis. The colonies had similar levels of genetic diversity with approximately half of the loci being polymorphic, an average of 1.6‐1.7 alleles per locus, and a mean heterozygosity per locus of approximately 18.4%. However, the colonies differed significantly in allele frequencies at the loci for phosphoglucomutase, glucose‐6‐phosphate dehydrogenase, xanthine oxidase, octanol dehydrogenase and phosphoglucose isomerase. The results were compared with earlier studies on this species and no evidence was found for selection of specific alleles during establishment or maintenance of colonies of G.pallidipes, nor were specific chromosomes, or marker genes, associated with the biological differences between the two colonies.